The Influence of Smart Tourism Destinations on Revisit Intention - Sugandini, Dyah; Oetomo, Hadi; Ambarwati, Sri Dwi Ari; Yodhatama, Muktiarya; Pamuji, Windy Anindya (Journal of International Conference Proceedings, 2023)
This research analyzes tourists’ revisit intentions at Indonesia’s Kulon Progo tourist attraction. Intention to revisit is predicted by smart tourism destination and destination image. The mediating effect of destination image on the intention to revisit is also analyzed in this research. This research is quantitative research using a survey of respondents. This study included 200 respondents who visited tourist destinations in the Kulonprogo area. The data analysis technique uses PLS-SEM. The research results show that the revisit intention model, influenced by smart tourism destination and destination image, is acceptable. Destination image affects directly to revisit intention. STD affects the destination image, and STD affects the revisit intention to Kulonprogo destination.